Iminências poéticas: Manoel de Barros e Arthur Bispo do Rosário por uma poética da recomposição de inutilidades e do acriançamento - Fernandes, Janice Aparecida de Azevedo (2015)
This research aimed to study post-modern artistic phenomenas, such as poetry made based on what would be dismissed as non-poetic or as consensual garbage. The proposal of the thematic is characterized as an exploratory bibliographic and phenomenological research, understanding on how the reframed resources used, the re-semanticizing given to the words and objects and the observation of a poetic self about such raw materials have certain linguistic, literary and poetic similarity. The research is justified by its degree of support for being a source for new researches on the subject which is now built. The authors analyzed for the study of this research were Manoel de Barros and Arthur Bispo do Rosário, the first, a poet and the second one an artist. The results found point to the fact that in both studied objects, it was observed the construction of their poetic linguistics for the deconstruction of art as a classic element and also of the ressignification that authors worked with, such as words and raw material throughout the re-composition of what is to be useless. It was able to point out how scientific contribution, the perception that although there are similarities between the studied authors, one has to consider what make them distant of each other, in this case, it´s their existential condition. Manoel de Barros simulated a poetic self totally childish that dazzles in front of the semantic possibilities of a word and it creates its own language, its Manoelês , marked by arquissemas . Poet that denatures the Pantanal, throughout poetic recomposition of the useless, creates a work in which language is the great theme , the great character . Arthur Bispo do Rosário was a schizophrenic on the sidelines of consumerism, invent the world on behalf of God, from a psychotic episode sending him to his own Divine Being. Theopoetics is the support of his work, a cataloged work as the world´s inventor. The research, " Poetic Eminences: Manoel de Barros and Arthur Bispo do Rosário - by the poetic recovery of the useless and childlike" was made possible by the financial support of the Fundação de Amparo à Pesquisa do Estado de Goiás (FAPEG).